The Economic Impact of Digital Competencies: A Fixed-Effects Panel Analysis for EU Countries - Krzysztof SIUDA (Communications of International Proceedings, 2025)
The main goal of this paper is to study the impact of digital competencies on economic growth measured by changes in the natural logarithm of GDP per capita. The study covers countries that are currently members of the European Union, and the data used to estimate the model spans the period from 2015 to 2019. To examine the relationship, a panel analysis was used. This method can isolate the impact of countries' time-invariant characteristics (fixed effects) as well as crises, business cycles, and shocks (time effects) common to all countries. The main explanatory variable for GDP per capita growth was a synthetic digital competence index created for the purposes of this study (Digital_Index). The baseline specification incorporated a number of control variables, which were subsequently removed in alternative specifications to assess changes in the quality of estimation. Models with and without lagged variables were used. A number of models with competency sub-indices and individual Internet and computer skills were tested. For the sake of comparison, OLS models were also estimated. The article indicates that digital competencies alone are not a determinant of economic growth in the short term, but this topic requires further research, the directions of which are pointed out in the conclusions.
Keywords: panel data analysis; fixed effects; digital competencies; digitalization